Vitamin E Modulates Cigarette Smoke Extract-induced Cell Apoptosis in Mouse Embryonic Cells - Zhao-Li Chen, Jian Tao, Jie Yang, Zhen-Li Yuan, Xing-Hua Liu, Min Jin, Zhi-Qiang Shen, Lu Wang, Hai-Feng Li, Zhi-Gang Qiu, Jing-Feng Wang, Xin-Wei Wang, Jun-Wen Li (International Journal of Biological Sciences, 2011)
Vitamin E (VE) can effectively prevent occurrence of lung cancer caused by passive smoking in mice. However, whether VE prevents smoking-induced cytotoxicity remains unclear. In this study, a primary culture of embryonic lung cells (ELCs) was used to observe the cytotoxic effects of cigarette smoke extract (CSE), including its influence on cell survival, cell cycle, apoptosis, and DNA damage, and also to examine the effects of VE intervention on CSE-induced cytotoxicity. Our results showed that CSE could significantly inhibit the survival of ELCs with dose- and time-dependent effects. Furthermore, CSE clearly disturbed the cell cycle of ELCs by decreasing the proportion of cells at the S and G2/M phases and increasing the proportion of cells at the G0/G1 phase. CSE promoted cell apoptosis, with the highest apoptosis rate reaching more than 40%. CSE also significantly caused DNA damage of ELCs. VE supplementation could evidently inhibit or reverse the cytotoxic effects of CSE in a dose- and time-dependent manner. The mechanism of CSE effects on ELCs and that of VE intervention might involve the mitochondrial pathway of cytochrome c-mediated caspase activation. Our study validate that VE plays a clearly protective effect against CSE-induced cytotoxicity in mouse embryonic lung cells.